Alpha-Angelica lactone in a new role: facile access to N-Aryl tetrahydroisoquinolinones and isoindolinones via organocatalytic alpha-CH2 oxygenation - Thatikonda, Thanusha; Deepake, Siddharth K.; Das, Utpal (Organic Letters, 2019)
A method for the direct oxidation of various N-aryl tetrahydroisoquinolines and isoindolines to the corresponding lactams using alpha-angelica lactone as a catalyst was developed. The utility of the method was further demonstrated by synthesis of indoprofen and indobufen.